1994
DOI: 10.1128/aem.60.12.4255-4262.1994
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Salmonella typhimurium in dairy products with flow cytometry and monoclonal antibodies

Abstract: Flow cytometry, combined with fluorescently labelled monoclonal antibodies, offers advantages of speed and sensitivity for the detection of specific pathogenic bacteria in foods. We investigated the detection of Salmonella typhimurium in eggs and milk. Using a sample clearing procedure, we determined that the detection limit was on the order of 10(3) cells per ml after a total analysis time of 40 min. After 6 h of nonselective enrichment, the detection limits were 10 cells per ml for milk and 1 cell per ml for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…Few studies have addressed the minimum concentration of bacteria detectable by flow cytometry, but limits in the region of 10 3 to 10 4 bacterial cells ml −1 are reportedly detectable using viability stains such as rhodamine 123 (Diaper and Edwards 1994) and nucleic acid stains such as ethidium bromide (Pinder et al 1990). The present authors have previously reported immunofluorescent labelling techniques which allow the detection of two species of salmonellas simultaneously, down to levels of 1×10 3 ml −1 in pure cultures (McClelland and Pinder 1994a), and 1×10 3 and 1×10 4 cells ml −1 in milk and egg, respectively (McClelland and Pinder 1994b ;Pinder and McClelland 1994). The total analysis time in all these cases was about 30 min.…”
Section: Introductionmentioning
confidence: 80%
“…Few studies have addressed the minimum concentration of bacteria detectable by flow cytometry, but limits in the region of 10 3 to 10 4 bacterial cells ml −1 are reportedly detectable using viability stains such as rhodamine 123 (Diaper and Edwards 1994) and nucleic acid stains such as ethidium bromide (Pinder et al 1990). The present authors have previously reported immunofluorescent labelling techniques which allow the detection of two species of salmonellas simultaneously, down to levels of 1×10 3 ml −1 in pure cultures (McClelland and Pinder 1994a), and 1×10 3 and 1×10 4 cells ml −1 in milk and egg, respectively (McClelland and Pinder 1994b ;Pinder and McClelland 1994). The total analysis time in all these cases was about 30 min.…”
Section: Introductionmentioning
confidence: 80%
“…This threshold, which occurred in the range of 10 4 organisms ml 31 , was similar to that reported in studies using FC to detect Salmonella spp. in eggs and milk [8]. Interestingly, the problem appeared to be unrelated to the fact that the samples were derived from a food matrix with a heterogeneous background £ora, since studies with mixtures of pure cultures in PBS had a similar lower limit of E. coli O157:H7 measurement.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to this problem has been the use of multiparameter analysis in which a strong £uorescence signal for all bacteria has been provided by nucleic acid binding dyes or by labeled antibody. A second £uorescence signal such as FITC was then used to identify the organism of interest [8]. Through the use of log-ampli¢ed FLS signals together with careful alignment and cleaning of optical and £uidic systems of the stream in quartz FC system we were able to achieve acceptable light scatter sensitivity without using nucleic acid binding dyes which would been incompatible with viable cell sorting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With experiments involving spiked milk samples, a Promega). The effect was to remove fat micelles from the milk, improving resolution of the bacteria (McClelland & Pinder, 1994b).…”
mentioning
confidence: 99%